Intensive measurements of gas, water, and energy exchange between vegetation and troposphere during the MONTES Campaign in a vegetation gradient from short semi-desertic shrublands to tall wet temperate forests in the NW Mediterranean basin - Penuelas, J; Guenther, A; Rapparini, F; Llusia, J; Filella, I; Seco, R; Estiarte, M; Mejia-Chang, M; Ogaya, R; Ibáñez, J; Sardans, J; Castaño, L M; et al. (Atmospheric Environment)
Abstract MONTES (“Woodlands”) was a multidisciplinary international field campaign aimed at measuring energy, water and especially gas exchange between vegetation and atmosphere in a gradient from short semi-desertic shrublands to tall wet temperate forests in NE Spain in the North Western Mediterranean Basin (WMB). The measurements were performed at a semidesertic area (Monegros), at a coastal Meditrerranean shrubland area (Garraf), at a typical Mediterranean holm oak forest area (Prades) and at a wet temperate beech forest (Montseny) during spring (April 2010) under optimal plant physiological conditions in driest-warmest sites and during summer (July 2010) with drought and heat stresses in the driest-warmest sites and optimal conditions in the wettest-coolest site. The objective of this campaign was to study the differences in gas, water and energy exchange occurring at different vegetation coverages and biomasses. Particular attention was devoted to quantitatively understand the exchange of biogenic volatile organic compounds (BVOCs) because of their biological and environmental effects in the WMB. A wide range of instruments (GC-MS, PTR-MS, meteorological sensors, O3 monitors,…) and vertical platforms such as masts, tethered balloons and aircraft were used to characterize the gas, water and energy exchange at increasing footprint areas by measuring vertical profiles. In this paper we provide an overview of the MONTES campaign: the objectives, the characterization of the biomass and gas, water and energy exchange in the 4 sites-areas using satellite data, the estimation of isoprene and monoterpene emissions using MEGAN model, the measurements performed and the first results. The isoprene and monoterpene emission rates estimated with MEGAN and emission factors measured at the foliar level for the dominant species ranged from about 0 to 0.2 mg m-2 h-1 in April. The warmer temperature in July resulted in higher model estimates from about 0 to ca 1.6 mg m-2 h-1 for isoprene and ca. 4.5 mg m-2 h-1 for monoterpenes, depending on the site vegetation and footprint area considered. There were clear daily and seasonal patterns with higher emission rates and mixing ratios at midday and summer relative to early morning and early spring. There was a significant trend in CO2 fixation (from 1 to 10 mg C m-2 d-1), transpiration (from x 1 to 5 kg C m-2 d-1), and sensible and latent heat from the warmest-driest to the coolest-wettest site. The results showed the strong land-cover-specific influence on emissions of BVOCs, gas, energy and water exchange, and therefore demonstrate the potential for feed-back to atmospheric chemistry and climate.
Keywords: aircraft; Boundary Layer; CH4; CO2; Evapotranspiration; green biomass; isoprene; lai; Land Cover; latent heat; masts; MEGAN; Monoterpenes; N2O; NDVI; O3; sensible heat; tethered balloons; Vegetation; vertical profiles; VOCs

Natural vegetation covers as indicators of the soil water content in a semiarid mountainous watershed - Gómez-Giráldez, Pedro J; Aguilar, Cristina; Polo, María José (Ecological Indicators, 2014)
This paper investigates the use of the vegetative state of natural covers as an indicator of soil moisture conditions at the end of the dry season in order to evaluate the cumulative effect of the hydrological regime. To achieve this, the three major vegetation covers in a mountainous semiarid environment in southern Spain were selected. Temporal and spatial trends of NDVI from Landsat-TM images were computed and related to the different hydrological patterns of variables in the study site, which were obtained with the hydrological WiMMed model. The heterogeneity in the hydrological behavior during the study period (914.5mm of annual rainfall in the wettest year (2009–2010) and 284.4mm in the driest year (2004–2005)) was reflected in the annual differences in NDVI values with steady mean NDVI values in coniferous vegetation (0.5–0.6) and more variable values in scrub cover. Both Correlation Analysis and Principal Component Analysis showed correlations among the different states of the vegetation cover, the variables involved in the soil water balance and those related to the snow dynamics of the antecedent year. Exponential fits were obtained between the mean annual soil water content and NDVI values with Pearson r2 coefficients of over 0.7 in scrub cover. In certain years, the best fits were also found in scrub cover with r2 values of up to 0.9. These results demonstrate the relationship between soil water content, the vigor of the natural vegetation and the hydrological characteristics of the antecedent year. The expressions obtained may serve to adjust the soil water content at the beginning of a hydrological year and to use the scrub cover as an indicator of the soil water balance in the area for a given year.
Keywords: Hydrological modeling; Landsat-TM; NDVI; Soil moisture; water stress; WiMMed

Start of the dry season as a main determinant of inter-annual Mediterranean forest production variations - Maselli, Fabio; Cherubini, Paolo; Chiesi, Marta; Gilabert, María Amparo; Lombardi, Fabio; Moreno, Alvaro; Teobaldelli, Maurizio; Tognetti, Roberto (Agricultural and Forest Meteorology, 2014)
Recent investigations have highlighted the dependence of Mediterranean forest production on spring rainfall. The current work introduces the concept of the start of the dry season (SDS) and performs a three-step analysis to determine the effect of SDS on Mediterranean forest production. Seven forest zones of Tuscany (Central Italy), which present differently pronounced Mediterranean features, are considered. First, a statistical analysis investigates the influence of spring water budget on forest Normalized Difference Vegetation Index (NDVI) inter-annual variations during July–August. The analysis is then extended to assess the impact of inter-annual SDS variability on forest gross primary production (GPP) simulated by a NDVI driven parametric model, modified C-Fix. These simulations lead to rank the considered forest types according to the relevance of SDS in regulating inter-annual GPP variations. The application of similar statistical analyses to detrended tree ring-width time series of typical Tuscany forests confirms the existence of an eco-climatic gradient in the functional relevance of SDS. The influence of SDS on tree growth is attenuated moving from Mediterranean arid to temperate humid environments. These findings are examined and interpreted from an eco-physiological viewpoint taking into consideration the peculiarity of Mediterranean forest ecosystems. Next, relevant implications are discussed in view of the possible consequences of ongoing climate change.
Keywords: Dry season; GPP; Mediterranean forests; Modified C-Fix; NDVI; Ring-widths

Leaf and stand-level carbon uptake of a Mediterranean forest estimated using the satellite-derived reflectance indices EVI and PRI - Garbulsky, Martín F.; Penuelas, Josep; Ogaya, Romà; Filella, Iolanda (International Journal of Remote Sensing, 2012)
Various aspects of global environmental change affect plant photosynthesis, the primary carbon input in ecosystems. Thus, accurate methods of measuring plant photosynthesis are important. Remotely sensed spectral indices can monitor in detail the green biomass of ecosystems, which provides a measure of potential photosynthetic capacity. In evergreen vegetation types, however, such as Mediterranean forests, the amount of green biomass changes little during the growing season and, therefore, changes in green biomass are not responsible for changes in photosynthetic rates in those forests. This study examined the net photosynthetic rates and the diametric increment of stems in a Mediterranean forest dominated by Quercus ilex using three spectral indices (normalized difference vegetation index (NDVI), enhanced vegetation index (EVI), and photochemical reflectance index (PRI)) derived from Moderate Resolution Imaging Spectroradiometer (MODIS) sensors. Average annual EVI accounted for 83% of the variability of the diametric increment of Q. ilex stems over a 10 year period. NDVI was marginally correlated with the diametric increment of stems. This study was the first to identify a significant correlation between net photosynthetic rates and radiation use efficiency at the leaf level using PRI derived from satellite data analysed at the ecosystem level. These results suggest that each spectral index provided different and complementary information about ecosystem carbon uptake in a Mediterranean Q. ilex forest.
doi: 10.1080/01431161.2012.718457doi: 10.1080/01431161.2012.718457The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: carbon uptake (voyant); EVI; mediterranean forest; NDVI; photochemical reflectance index (PRI)

Trends in the surface vegetation dynamics of the national parks of Spain as observed by satellite sensors - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José M.; Delibes, Miguel (Applied Vegetation Science, 2008)
Questions: What are the current dynamics, as observed by synoptic sensors, of surface vegetation in Spanish protected areas? Are these areas and their vegetation types uniformly affected by the increase in vegetation greenness detected throughout Europe? Location: Iberian National Parks of Spain. Methods: We used the normalized difference vegetation index (NDVI) from global inventory modeling and mapping studies (GIMMS) advanced very high resolution radiometer (AVHRR) dataset to monitor surface vegetation. NDVI is a surrogate for the photosynthetically active radiation absorbed by vegetation (fAPAR). This functional attribute has a short-time response to disturbances, is connected to ecosystem services and can be monitored through remote sensing. First, we provide a baseline description of the NDVI dynamics in the parks and analysed its temporal trends (1981-2003). Then, we evaluated the relationships of the seasonal dynamics and interannual trends with the climate conditions, vegetation types and conservation histories of the parks. Results: The parks showed two patterns of NDVI dynamics corresponding to Mediterranean and Eurosiberian regions. Most parks showed areas with positive NDVI trends that tended to have higher proportions of Mediterranean coniferous and mixed forests, oro-Mediterranean scrublands, heathlands, maquis and garrigues. Negative trends were scarce and associated with marshes and Alpine coniferous forests. The lack of a common response in all parks was related to their different environmental conditions, management, and conservation histories. Conclusions: National parks are changing in the short term but not uniformly. This study represents a basis for the incorporation of functional attributes of ecosystems in the management and monitoring of protected areas in the face of global change.
Keywords: Global environmental change; monitoring; National Park conservation; NDVI; Remote sensing.

Trends in the surface vegetation dynamics of the national parks of Spain as observed by satellite sensors - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José M; Delibes, Miguel (Applied Vegetation Science, 2008)
Questions: What are the current dynamics, as observed by synoptic sensors, of surface vegetation in Spanish protected areas? Are these areas and their vegetation types uniformly affected by the increase in vegetation greenness detected throughout Europe? Location: Iberian National Parks of Spain. Methods: We used the normalized difference vegetation index (NDVI) from global inventory modeling and mapping studies (GIMMS) advanced very high resolution radiometer (AVHRR) dataset to monitor surface vegetation. NDVI is a surrogate for the photosynthetically active radiation absorbed by vegetation (fAPAR). This functional attribute has a short-time response to disturbances, is connected to ecosystem services and can be monitored through remote sensing. First, we provide a baseline description of the NDVI dynamics in the parks and analysed its temporal trends (1981-2003). Then, we evaluated the relationships of the seasonal dynamics and interannual trends with the climate conditions, vegetation types and conservation histories of the parks. Results: The parks showed two patterns of NDVI dynamics corresponding to Mediterranean and Eurosiberian regions. Most parks showed areas with positive NDVI trends that tended to have higher proportions of Mediterranean coniferous and mixed forests, oro-Mediterranean scrublands, heathlands, maquis and garrigues. Negative trends were scarce and associated with marshes and Alpine coniferous forests. The lack of a common response in all parks was related to their different environmental conditions, management, and conservation histories. Conclusions: National parks are changing in the short term but not uniformly. This study represents a basis for the incorporation of functional attributes of ecosystems in the management and monitoring of protected areas in the face of global change.
Keywords: Global environmental change; monitoring; National Park conservation; NDVI; Remote sensing.

Detection of Forest Decline Using IKONOS Sensor for Cork Oak (Quercus suber L.) Woods in South Spain - Cano, Francisco; Cerrillo, Rafael Ma Navarro; Ferrer, Alfonso Garcia; de la Orden, Manuel Sanchéz (Geocarto International, 2006)
Abstract Assessment of forest decline is severely hampered by the limited information on tree death on short temporal and broad spatial scales. In order to evaluate forest decline rates in cork oak of Southern Spain, an analysis was made of statistical correlation between the 4 IKONOS sensor original bands acquired in 2000, the Normalized Difference Vegetation Index (NDVI) and Infrared/Red Index (IR/R) and defoliation information obtained from the ground study. IKONOS near infrared band was negative correlated with defoliation (Pearson Correlation ? 0.762). The correlation between defoliation and IR/R ratio (Pearson Correlation ?0.506) and NDVI (Pearson Correlation ?0.449) was also significantly correlated. The dispersion of data presents in each category of defoliation justifies the use of the median value as the representative variable value for each intervals of defoliation. The Statistical Index of Defoliation (SID), generated from a lineal combination of IKONOS sensor bands, shows a correlation rate of 0.85 with the deforestation ground estimate. This study shows that high?spatial?resolution satellite data can now be used to measure forest decline processes, suggesting many new alternatives to evaluate the impact of forest decline in Mediterranean forests.
doi: 10.1080/10106040608542388
Keywords: defoliation; Forest decline; IKONOS (PG); Infrared/RedIndex (IR/R); NDVI; Statistical Index of Defoliation (SID)

Detection of Forest Decline Using IKONOS Sensor for Cork Oak (Quercus suber L.) Woods in South Spain - Cano, Francisco; Cerrillo, Rafael Ma Navarro; Ferrer, Alfonso Garcia; de la Orden, Manuel Sanchéz (Geocarto International, 2006)
Abstract Assessment of forest decline is severely hampered by the limited information on tree death on short temporal and broad spatial scales. In order to evaluate forest decline rates in cork oak of Southern Spain, an analysis was made of statistical correlation between the 4 IKONOS sensor original bands acquired in 2000, the Normalized Difference Vegetation Index (NDVI) and Infrared/Red Index (IR/R) and defoliation information obtained from the ground study. IKONOS near infrared band was negative correlated with defoliation (Pearson Correlation ? 0.762). The correlation between defoliation and IR/R ratio (Pearson Correlation ?0.506) and NDVI (Pearson Correlation ?0.449) was also significantly correlated. The dispersion of data presents in each category of defoliation justifies the use of the median value as the representative variable value for each intervals of defoliation. The Statistical Index of Defoliation (SID), generated from a lineal combination of IKONOS sensor bands, shows a correlation rate of 0.85 with the deforestation ground estimate. This study shows that high?spatial?resolution satellite data can now be used to measure forest decline processes, suggesting many new alternatives to evaluate the impact of forest decline in Mediterranean forests.
doi: 10.1080/10106040608542388doi: 10.1080/10106040608542388The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: defoliation; Forest decline; IKONOS (PG); Infrared/RedIndex (IR/R); NDVI; Statistical Index of Defoliation (SID)

Influence of fire severity on plant regeneration by means of remote sensing imagery - Díaz-Delgado, R; Lloret, F; Pons, X (International Journal of Remote Sensing, 2003)
In this paper we analyse the interactions between fire severity (plant damage) and plant regeneration after fire by means of remote sensing imagery and a field fire severity map. A severity map was constructed over a large fire (2692 ha) occurring in July 1994 in the Barcelona province (north-east of Spain). Seven severity classes were assigned to the apparent plant damage as a function of burning intensity. Several Landsat TM and MSS images from dates immediately before and after the fire were employed to monitor plant regeneration processes as well as to evaluate the relationship with fire severity observed in situ . Plant regeneration was monitored using NDVI measurements (average class values standardized with neighbour unburned control plots). Pre-fire NDVI measurements were extracted for every plant cover category (7), field fire severity class (7), and spatial cross-tabulation of both layers (33) and compared to post-fire values. NDVI decline due to fire was positively correlated with field fire severity class. Results show different patterns of recovery for each dominant species, severity class and combination of both factors. For all cases a significant negative correlation was found between damage and regeneration ability. This work leads to a better understanding of the influence of severity, a major fire regime parameter on plant regeneration, and may aid to manage restoration on areas burned under different fire severity levels.
doi: 10.1080/01431160210144732
Keywords: dominant species (voyant); fire severity; NDVI; plant damage; plant regeneration

Influence of fire severity on plant regeneration by means of remote sensing imagery - Díaz-Delgado, R.; Lloret, F.; Pons, X. (International Journal of Remote Sensing, 2003)
In this paper we analyse the interactions between fire severity (plant damage) and plant regeneration after fire by means of remote sensing imagery and a field fire severity map. A severity map was constructed over a large fire (2692 ha) occurring in July 1994 in the Barcelona province (north-east of Spain). Seven severity classes were assigned to the apparent plant damage as a function of burning intensity. Several Landsat TM and MSS images from dates immediately before and after the fire were employed to monitor plant regeneration processes as well as to evaluate the relationship with fire severity observed in situ . Plant regeneration was monitored using NDVI measurements (average class values standardized with neighbour unburned control plots). Pre-fire NDVI measurements were extracted for every plant cover category (7), field fire severity class (7), and spatial cross-tabulation of both layers (33) and compared to post-fire values. NDVI decline due to fire was positively correlated with field fire severity class. Results show different patterns of recovery for each dominant species, severity class and combination of both factors. For all cases a significant negative correlation was found between damage and regeneration ability. This work leads to a better understanding of the influence of severity, a major fire regime parameter on plant regeneration, and may aid to manage restoration on areas burned under different fire severity levels.
doi: 10.1080/01431160210144732doi: 10.1080/01431160210144732The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: dominant species (voyant); fire severity; NDVI; plant damage; plant regeneration

Monitoring Leaf Area Index of Mediterranean oak woodlands: Comparison of remotely-sensed estimates with simulations from an ecological process-based model - Garson, D. Caraux; LACAZE, B. (International Journal of Remote Sensing, 2003)
Annual vegetation abundance mapping was carried out within the DeMon II European project over a period of 12 years (1984-1996). The project relied on advanced satellite-based methods for spatial and temporal monitoring of Mediterranean oak woodlands by means of a series of Landsat Thematic Mapper (TM) satellite data. A standardized approach developed previously focuses on the Languedoc site, Hautes Garrigues, a typical sensitive Mediterranean region, but now recovering after centuries of grazing and agricultural activities. After geometric and radiometric rectification of nine full Landsat TM scenes with a refined correction in a smaller area of 75 km 2 75 km, a GIS database was created containing satellite data, thematic maps of vegetation, geological maps, climatic data and field measurements. An empirical relation between radiometric ground truth measurements and satellite derived Normalized Difference Vegetation Index (NDVI) allows us to derive Leaf Area Index (LAI). An ecological process-based model (Forest BGC) has been adapted to simulate ecosystem processes in a satisfying way at a local scale. Consistent results were obtained from remote sensing data and from simulations at a local scale, suggesting the possible use of remote-sensing data to monitor vegetation abundance changes at a regional scale. Without considering human disturbances, it can be noted that not much variation of LAI induced by natural factors can be detected over the considered 12-year period.
doi: 10.1080/0143116021000024267doi: 10.1080/0143116021000024267The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Annual variation (voyant); green vegetation; Leaf area index (LAI); NDVI; Oak woodlands; Remote sensing

Monitoring Leaf Area Index of Mediterranean oak woodlands: Comparison of remotely-sensed estimates with simulations from an ecological process-based model - Garson, D Caraux; Lacaze, B (International Journal of Remote Sensing, 2003)
Annual vegetation abundance mapping was carried out within the DeMon II European project over a period of 12 years (1984-1996). The project relied on advanced satellite-based methods for spatial and temporal monitoring of Mediterranean oak woodlands by means of a series of Landsat Thematic Mapper (TM) satellite data. A standardized approach developed previously focuses on the Languedoc site, Hautes Garrigues, a typical sensitive Mediterranean region, but now recovering after centuries of grazing and agricultural activities. After geometric and radiometric rectification of nine full Landsat TM scenes with a refined correction in a smaller area of 75 km 2 75 km, a GIS database was created containing satellite data, thematic maps of vegetation, geological maps, climatic data and field measurements. An empirical relation between radiometric ground truth measurements and satellite derived Normalized Difference Vegetation Index (NDVI) allows us to derive Leaf Area Index (LAI). An ecological process-based model (Forest BGC) has been adapted to simulate ecosystem processes in a satisfying way at a local scale. Consistent results were obtained from remote sensing data and from simulations at a local scale, suggesting the possible use of remote-sensing data to monitor vegetation abundance changes at a regional scale. Without considering human disturbances, it can be noted that not much variation of LAI induced by natural factors can be detected over the considered 12-year period.
doi: 10.1080/0143116021000024267
Keywords: Annual variation (voyant); green vegetation; Leaf area index (LAI); NDVI; Oak woodlands; Remote sensing

The NDVI and spectral decomposition for semi-arid vegetation abundance estimation - Hurcom, S J; Harrison, A R (International Journal of Remote Sensing, 1998)
This paper describes the use of the Normalized Difference Vegetation Index (NDVI) and spectral decomposition techniques to estimate vegetation abundance using ground-based spectroradiometric data of semi-arid vegetation. It is found that the NDVI provides a better measure of the proportion of directly irradiated leaves within the field-of-view of the spectroradiometer than it does the Leaf Area Index or biomass. Moreover, it is found that spectral decomposition isolates a factor which is strongly influenced by spectral variation at the region of the red edge. This factor is highly correlated with the NDVI -(R2=0.91) and as such also provides a good estimate of the proportion of directly irradiated leaves. It is suggested that spectral decomposition techniques provide a unique framework in which to analyse the factors affecting the spectral response of vegetation.
doi: 10.1080/014311698214217
Keywords: LAI (voyant); NDVI; spectral decomposition; vegetation abundance

Estimation of plant water concentration by the reflectance Water Index WI (R900/R970) - Penuelas, J; Piñol, J; Ogaya, R; Filella, I (International Journal of Remote Sensing, 1997)
Abstract Water Index WI (R900/R970) was used for the estimation of plant water concentration (PWC) by ground-based, reflectance measurements. Reflectance and PWC were measured for adult plants growing in the field throughout an annual cycle and in potted seedlings submitted to progressive desiccation. The species studied were characteristicly Mediterranean: Pinus halepensis, Quercus ilex, Quercus coccifera, Arbutus unedo, Cistus albidus, Cistus monspeliensis, Phillyrea angustifolia, Pistacia lentiscus and Brachypodium retusum . WI was significantly correlated with PWC when all the species were considered together, and with almost all the species considered individually, especially when a wider range of PWC was obtained by extreme dessication of experimental plants. The correlations increased when normalizing WI by NDVI. The wavelength of the trough corresponding to water absorption band tended to shift from 970-980 nm to lower wavelengths 930-950 nm with decreasing PWCs. Infrared measurement of plant temperature and T leaf - T air provided worse assessment of PWC. A simple radiometer measuring plant reflectance at 680, 900, and 970nm could speed up the measurement of PWC, and be useful in wildfire risk evaluation and drought assessment.
doi: 10.1080/014311697217396
Keywords: Mediterranean plant species (voyant); NDVI; plant water concentration (PWC); water index